Kompetisi dan Posisi Tubuh Perempuan dalam Iklan Rokok: Analisis Wacana Kritis Pada Novel “Gadis Kretek” Karya Ratih Kumala - Indriani, Laillia Dhiah (Sasdaya: Gadjah Mada Journal of Humanities, 2023)
Using women's bodies in product marketing advertisements is nothing new. The female body is deliberately presented as a marketing strategy. In practice, it is not uncommon for women to be categorized into three trinities, namely, girl, wife, and entertainer. What's worse, this is justified and reproduced by various media. The Gadis Kretek novel is a literary work that juxtaposes the female body with cigarette advertisements. This research was conducted to uncover how women's bodies are selected, used, and displayed for marketing activities of cigarette products that are attached to men by society and become a symbol of masculinity. The method that will be used as a data analysis tool is Norman Fairclough's critical discourse analysis, which focuses on aspects of linguistic practice, discursive practice, and social practice. The results of this study indicate that in product promotion, the female body is used as a desire production machine that will attract potential buyers. Women in ad frames are also categorized based on the Girl-Wife-Entertainer trinity, where the three of them have their own identities but are still presented as complements to men. From this research, it can be seen that literary works also commodify discourses on beauty and the female body. The female body seems to be an affirmation of the construction of masculinity.